(3fNH ef cJGH GdLeGgjQ aj GdLhGgQs - (3eLghds ((3eMeO Hf bWH GdWHjH s)
(3ChdgG (B:s
(3bGd ai GdjGbhJ (B: (3GSeg HGdaGQSjI jGcfO hGdaQS jdbHhfg eSHM GaShM Edi OGaY GdWGYhf hgh SHM HGdaGQSjI s
(3BNQgG (B:s
(3GdWGdbhf hbO jLF ai GdcJH PcQ GdWGdbhf ef ZjQ GaUGM ajgG fLRJ GdebGdI hJe HgG GdcJGHg s
(3hQO GdYfhGf GdCUdi ai cX (B1/ 594s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJjGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs